Seasonal and Spatial Differences in Metal and Metalloid Concentrations in the Snow Cover of Hansbreen, Svalbard - Koziol, Krystyna; Uszczyk, Aleksander; Pawlak, Filip; Frankowski, Marcin; Polkowska, Żaneta (Frontiers in Earth Science, 2021)
Metals and metalloids in snow on glaciers, depending on the season of deposition, may come from various sources: local rock dust (erosion of the geological substratum), marine aerosol, local human activity (e.g. fuel combustion, waste incineration) and long-range atmospheric transport. Hansbreen glacier, located close to the Polish Polar Station in Svalbard, is a perfect site to study metals and metalloids: it has complex geological substratum, a year-round presence of a small group of people, and is near the coast. We analysed a snapshot of elemental concentrations in snow samples from shallow cores corresponding to autumn, winter and spring deposition on Hansbreen. Eighteen cores of snow were collected across the glacier, revealing the influence of potential local pollution sources. In these samples, we predominantly found Na, Mg and K, followed by Zn, Ca, Al and Fe. Heavy metals (Bi, Hg) were also detected. Cluster analysis of the determined elemental concentrations divided them into three distinct groups: 1) Ag, As, Bi, Cd, Hg, Mo, Sb, Se and Zn – representing mostly long-range transported volatile elements, with possible extra local geological sources; 2) Al, Fe, Cu and Mn – elements with crustal sources, and 3) Na, Ca, Mg, K and Sr – mainly from sea spray aerosol. Such interpretation was confirmed by the calculation of sea salt contribution based on mean seawater composition. In the study site, snow was up to six times more efficient in bringing metal and metalloid pollution into terrestrial environment, when comparared to rain.